Pigment properties of new and high-quality inbred lines and hybrids of maize with high nutritional values - Radenovic, C.N.; Grodzinskij, D.M.; Saratlic, G.N.; Miric, M.D.; Beljanski, M.V. (Физиология растений и генетика, 2015)
This paper presents results of different studies on confirmation of a hypothesis that maize inbred lines rich in pigments and with exceptional nutritive values can be bred in order to support a medicinal standpoint of programmed need for maize in food and feed. With such an experimental approach the following maize inbreds: ZPPL 146 and ZPPL 159 and hybrids derived from them: ZP 633, ZP 735 and ZP 737 have been systematically tested. Conformational characteristics of carotenoid molecules in leaves were established by means of the resonance Raman spectroscopy. Inbread lines and hybrids which are rich in carotenoids also contain other beneficial biologically active substances. Викладено результати досліджень, які підтверджують правомірність гіпотези про те, що інбредні лінії кукурудзи з підвищеним вмістом пігментів і високими поживними якостями можуть бути основою для отримання гібридів, що повною мірою відповідають сучасним вимогам до продуктів харчування та кормів. У цьому плані всебічно вивчено інбредні лінії кукурудзи ZPPL 146, ZPPL 159 й отримані на їх основі гібриди ZP 633, ZP 735, ZP 737. Конформаційні характеристики молекул каротиноїдів у листку отримано за допомогою резонансної раманівської спектроскопії. З’ясувалося, що інбредні лінії і гібриди з високою концентрацією каротиноїдів містять у зернівках й інші корисні біологічно активні речовини. Представлены результаты исследований, подтверждающие правомерность гипотезы о том, что инбредные линии кукурузы с повышенным содержанием пигментов и высокими питательными качествами могут быть основой для получения гибридов, в полной мере соответствующих современным требованиям к продуктам питания и кормам. В этом плане всесторонне изучены инбредные линии кукурузы ZPPL 146, ZPPL 159 и полученные на их основе гибриды ZP 633, ZP 735, ZP 737. Конформационные характеристики молекул каротиноидов в листьях получены с помощью резонансной рамановской спектроскопии. Оказалось, что инбредные линии и гибриды с высокой концентрацией каротиноидов содержат в зерновках и другие полезные биологически активные вещества. These studies have been mainly financially supported by the Maize Research Institute, Zemun Polje, Belgrade and partly by the Ministry of Education, Science and Technological Development of the Republic of Serbia (Projects 03E211, 03E22, 172015, TR-20003, TR- 20007, TR-20014).